IMPROVEMENT OF THE METHOD OF TEACHING CALCULATION OF STRENGTH LIMITS OF REINFORCED CONCRETE BEAMS - Sadikova Khurshidabonu Toychiboy kizi (Western European Studies, 2025)
This article analyzes the shortcomings of current teaching methods for studying surface stress and deformation states in reinforced concrete beams, as well as the causes of their exposure to bending moments and shear forces during earthquakes. It then describes a proposed methodology based on problem-based learning, competency-based approaches, numerical modeling, and practical calculation examples. This approach aims to foster engineering thinking, integrate theoretical knowledge with practical applications, and develop students' independent calculation skills
Keywords: seismic; Eurocode; reinforced concrete